Effects of experimental lightgaps and topography on enrichment plantings in a central amazonian secondary forest - Bentos, Tony V.; Nascimento, Henrique Eduardo Mendonça; Vizcarra, Marisângela dos Anjos; Williamson, G. Bruce (Acta Amazonica, 2020)
Enrichment plantings into secondary forest are an important option in restoring species diversity and ecosystem services. However, little attention has been given to environmental requirements for species performance. This study evaluated the effects of lightgaps and topographic position on the growth and survival of four native tree species (Pouteria caimito, Garcinia macrophylla, Dipteryx odorata and Cynometra bauhiniaefolia) planted into a 26-year old secondary forest originating from abandoned pastures in the central Amazon Basin. Artificial lightgaps and control plots under closed canopy were uniformly distributed on plateaus and bottomlands near water bodies. Seedlings were planted randomly into the plots and monitored for 28 months. Seedling survival rate was high (93%) and did not differ among species. Overall, lightgaps produced a 38% increase in seedling height relative to the controls. Although the four species naturally occur in mature forest, two of the four grew significantly more in lightgaps than in closed canopy secondary forest. Overall, bottomlands facilitated greater seedling growth in height (38%) relative to plateaus, but only one species exhibited a significant increase. This study shows the importance of the environmental variability generated with canopy openings along the topographic gradient, suggesting that both the selection of species and microsite conditions of planting sites have to be considered important criteria in the recovery of degraded areas. © 2020, Instituto Nacional de Pesquisas da Amazonia. All rights reserved.
Efeitos de clareiras experimentais e da topografia sobre plantios de enriquecimento em uma floresta secundária na amazônia central
Keywords: Abandoned Pastures; Environmental Conditions; Height growth; Light Availability